Analysis Of Dynamic Stability Of Synchronous Generators In Hydro Power Station In The Electrical Energy System In The Matlab Software - To‘xtashev Alisher Akmaljon o‘g‘li; Xalilov Islomjon G‘ulomjon o‘g‘li (Genius Journals, 2023)
The article presents the equations of stability of the electric power system, the asynchronous mode and the asynchronous state of the system. A model of the differential equation in the Matlab program is constructed and the necessary results are obtained.
Keywords: static and dynamic stagnation; ynchronous and asynchronous mode